Profiles of water quality at Menjangan Besar Island, Karimunjawa, Central Java Province, Indonesia - BAMBANG SULARDIONO; CHURUN A’IN; MAX RUDOLF MUSKANANFOLA (Biodiversitas Journal of Biological Diversity, 2018)
Sulardiono B, A’in C, Muskananfola MR. 2018. Profiles of water quality at Menjangan Besar Island, Karimunjawa, Central Java Province, Indonesia. Biodiversitas 19: 2308-2315. The development of anthropogenic and tourism activities causes the ecological impact on water quality. The profile of water quality and sediment are the representation of environmental condition of ecosystems, then they could be indicators of pollution, fertility, suitability, and environmental carrying capacity on marine life. This study aimed to characterize the environmental indicator based on the quality profile of Menjangan Besar waters, Karimunjawa, Central Java. Data collection using a purposive sampling method based on water and sediment characteristics in Menjangan Besar waters. The research location is divided into three stations, namely: station A: the waters of fish cage activity; station B: floating guesthouse activity; and station C: seaweed marine culture. Variable on water quality profile consists of N-NO3 (mg/L) and PO4-P (mg/L), chlorophyll-? (mg/m3), and bacterial (CFU/mL), and other water quality support, while the variables on sediment quality profile consist of Phosphorus (mg/g) and PO4-P (mg/g), organic (%), C-organic (%) and bacterial (CFU/g), and sediment grain size. The calculation data analysis method of water and sediment total bacteria profile used Total Plate Count (TPC) by following SNI 7545.1 (2009), while analysis for nitrification bacteria (Nitrosomonas and Nitrobacter) using Most Probable Number (MPN). Data analysis of sediment grains size used two methods, i.e. (i) dry mechanic method by using sieve shaker, and (ii) wet mechanic method by using a pipette. Data analysis of nitrate and phosphate using Brucine Sulfanilik method. Mapping of the spatial distribution of measurement data for water nutrient contents (NO3-N and PO4-P), bacteria, and Chlorophyll-? in the waters using ArcGIS software application tool. The results showed that nitrification bacteria content in the water column is lower than in the sediments layer. Total bacteria content in both the water column and sediment layer varies between stations. Total bacteria in station A is higher than the other stations. The water nutrient content (Nitrate and Phosphate) is still above the quality standard for Marine Biota (Kepmen LH No. 51/2004). The condition of the fertility of Menjangan Besar waters is oligotrophic tend to mesotrophic, in the sense that the waters quality is low to medium conditions, and not yet dangerous for marine biota.